(untitled) (European Journal of Health Research, 2025)
Introduction: Adolescence is a critical developmental stage where nutrition plays a vital role in growth and long-term health. Despite this, many adolescents fail to meet dietary recommendations, resulting in poor diet quality and increased risk of malnutrition and non-communicable diseases. Objective: To examine the associations between diet quality and nutrition knowledge among in-school adolescents in private and public schools in Odeda Local Government Area, Ogun State, Nigeria.. Methodology: A descriptive cross-sectional design was employed, involving 402 adolescents aged 13–17 years selected through multi-stage random sampling from two public and two private schools. Dietary intake was assessed using the Global Diet Quality Project tool, while nutrition knowledge was measured with a validated questionnaire. Data were analyzed using descriptive statistics, chi-square tests, and multiple regression at p < 0.05 significance level. Results: The mean age of respondents was 15.24 ± 1.03 years, with females comprising 65.2%. While 56.5% of adolescents had adequate dietary diversity, 84.8% fell below global dietary recommendations. Nutrition knowledge was moderate in 73.6%, good in 15.4%, and poor in 10.9%. Private school students had significantly higher nutrition knowledge (p = 0.001), though no significant differences were found in dietary diversity or adherence to dietary recommendations between school types. Multiple regression revealed that household position (p = 0.001) and number of siblings (p = 0.025) significantly predicted dietary diversity, while gender (p = 0.014) and maternal education (p = 0.020) predicted adherence to global dietary recommendations. Conclusion: Adolescents in Odeda LGA showed moderate dietary diversity but poor adherence to global dietary recommendations. While private school students demonstrated slightly better nutrition knowledge, overall diet quality was inadequate. These associations, given the cross-sectional design, should be interpreted with caution. Further longitudinal and interventional studies are needed to better understand and address adolescent dietary behaviors.